The combination of polystyrene microplastics and di (2-ethylhexyl) phthalate promotes the conjugative transfer of antibiotic resistance genes between bacteria - Yu Li; Xiaomei Liu; Saisai Guo; Lan Wang; Jingchun Tang (Ecotoxicology and Environmental Safety)
Plastic pollution has become a common phenomenon. The process of plastic degradation is accompanied by the release of microplastics and plasticizers. However, the coexistence of microplastics and plasticizers on the transfer of antibiotic resistance genes (ARGs) has not been reported until now. Here, polystyrene (PS) microplastics and plasticizer di (2-ethylhexyl) phthalate (DEHP) were used for combined treatment experiment and their effects and mechanisms on the transfer of ARGs between bacteria were explored. By increasing cell membrane permeability and the expression of correlated genes, the combined treatment group showed promoting effects on the transfer of ARGs than that of control, with the highest promoting effects observed at 1 mg/L PS and 0.1 mg/L DEHP, which was 3.0 times higher in ARGs transfer rate than that of control. It was found that PS and DEHP treatment alone also led to a higher conjugative transfer frequency, and the frequency of the combined treatment was lower than that of the corresponding single treatment group. This indicated that the effects of DEHP and microplastics on ARGs transfer might be antagonistic. Transcriptome analysis indicated that the transfer of ARGs affects bacterial ion binding, oxidative stress, and energy metabolism processes, while the expression of genes related to cell membrane permeability, DNA repair, bacterial drug resistance, and quorum sensing also increase. This study may provide new insights for explaining the combined effects of various pollutants in the environment on the spread of ARGs.